Critical time for weed removal in glyphosate-resistant soybean as influenced by preemergence herbicides. (June 2019) - Knezevic, Stevan Z.; Pavlovic, Pavle; Osipitan, O. Adewale; Barnes, Ethann R.; Beiermann, Clint; Oliveira, Maxwel C.; Lawrence, Nevin; Scott, Jon E.; Jhala, Amit
Abstract: Widespread and repeated use of glyphosate resulted in an increase in glyphosate-resistant (GR) weeds. This led to an urgent need for diversification of weed control programs and use of PRE herbicides with alternative sites of action. Field experiments were conducted over a 4-yr period (2015 to 2018) across three locations in Nebraska to evaluate the effects of PRE-applied herbicides on critical time for weed removal (CTWR) in GR soybean. The studies were laid out in a split-plot arrangement with herbicide regime as the main plot and weed removal timing as the subplot. The herbicide regimes used were either no PRE or premix of either sulfentrazone plus imazethapyr (350 + 70 g ai ha −1 ) or saflufenacil plus imazethapyr plus pyroxasulfone (26 + 70 + 120 g ai ha −1 ). The weed removal timings were at V1, V3, V6, R2, and R5 soybean stages, with weed-free and weedy season-long checks. Weeds were removed by application of glyphosate (1, 400 g ae ha −1 ) or by hoeing. The results across all years and locations suggested that the use of PRE herbicides delayed CTWR in soybean. In particular, the CTWR without PRE herbicides was determined to be around the V1 to V2 (14 to 21 d after emergence [DAE]) growth stage, depending on the location and weed pressure. The use of PRE-applied herbicides delayed CTWR from about the V4 (28 DAE) stage up to the R5 (66 DAE) stage. These results suggest that the use of PRE herbicides in GR soybean could delay the need for POST application of glyphosate by 2 to 5 wk, thereby reducing the need for multiple applications of glyphosate during the growing season. Additionally, the use of PRE herbicides could provide additional modes of action needed to manage GR weeds in GR soybean.